Fotografi Arsitektur Eksterior dan Landscape di Perkotaan - Rhodys Ndoen; Julia S. P. L Baok; Hendricus Herry Cornelis; Gede Krisnantara; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Photography starts from recording a reality into the medium of storage as accurately as possible. In line with the development of human life, photography also developed, among others, into a medium of artistic expression, including in architectural photography. Urban landscape is a term that refers to something related to urban exploration. Urban itself means an area that serves as a residence, a central distribution that has self-government, and economic activities based not just on agriculture. It can be said that urban landscape photography shows a picture of the area with the situation in an urban area or suburb. By looking at urban landscape photography we can see record events and atmosphere in an area consisting of roads, buildings, parks, and infrastructure that supports the people in it. Night Photography is a type of theme flow in The Art of Photography that makes the natural panorama at night a beautiful and interesting photo object. Night Photography or Photography Tonight presents a night atmosphere or Landcape conditions at night decorated with light grains of lights or stars in the sky.